2020
DOI: 10.3389/feart.2020.00158
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic Characterization of Raw Material Sources at Oldupai Gorge, Tanzania

Abstract: Oldupai Gorge is located within the Ngorongoro Conservation Area, a UNESCO World Heritage Site in northern Tanzania along the western margin of the East African Rift System. Oldupai's sedimentary record contains inter-stratified stone tool industries associated with the Earlier, Middle, and Later Stone Age. While diachronic technological change is perceptible, the totality of locally available rocks remained largely unchanged through time. Here, thin section petrography, Scanning Electron Microscopy-Energy Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…First, in every phase, lithic technology was produced mostly on quartzite, with other materials being less frequent. Macroscopic and petrographic data, compared to published reference collections (Favreau et al, 2020;Soto et al, 2020a,b), determined that the most likely sources for the raw materials employed at Ewass Oldupa were the outcrops of Naisiusiu, Naibor Soit, Endonyo Osunyai, and/or Oittii. However, chemical characterization and Linear Discriminant Analysis of Oldowan materials showed that up to three-quarters of the quartzite came from Naibor Soit, while strictly local rock from Naisiusiu was less commonly employed (Mercader et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…First, in every phase, lithic technology was produced mostly on quartzite, with other materials being less frequent. Macroscopic and petrographic data, compared to published reference collections (Favreau et al, 2020;Soto et al, 2020a,b), determined that the most likely sources for the raw materials employed at Ewass Oldupa were the outcrops of Naisiusiu, Naibor Soit, Endonyo Osunyai, and/or Oittii. However, chemical characterization and Linear Discriminant Analysis of Oldowan materials showed that up to three-quarters of the quartzite came from Naibor Soit, while strictly local rock from Naisiusiu was less commonly employed (Mercader et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To this day, the combination of macroscopic and petrographic techniques has proven useful to delineate similarities and differences among quartzitic outcrops at Oldupai Gorge. For instance, two recent studies using a combination of macroscopic, petrographic, and geochemical techniques have shown that green quartzites are exclusive to two outcrops on a local scale, a fact that was corroborated by the petrographic identification of the mineral fuchsite that is responsible for the green colour in hand sample (Favreau et al 2020;Soto et al 2020a). The validation that quartz-rich outcrops can be differentiated from one another based on macroscopic and petrographic data is in line with a growing body of literature that counters the implicit assumption that it is unachievable on any spatial scale (e.g.…”
Section: From Macroscopic To Petrographic Characterisationmentioning
confidence: 93%
“…Moreover, some of these rhyolites were exposed to metasomatism by carbonatite magmatic doming in which additional elements were introduced into the rocks by circulating fluids (Finestone et al 2020). The HWK E site at Oldupai Gorge (Tanzania) (Figure 2) has yielded one Oldowan lithic manufactured from "altered but unmetamorphosed gabbro" (Hay 1976:185) that may be provenanced to the Tanzania Craton, although a closer Neoproterozoic outcrop has been proposed as an alternative source based on a petrogenetic analogue (Favreau et al 2020).…”
Section: Geology and Raw Materials Of Eastern Africamentioning
confidence: 99%
See 2 more Smart Citations